2003
DOI: 10.1523/jneurosci.23-11-04428.2003
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical Long-Term Potentiation and Experience-Dependent Synaptic Plasticity Require α-Calcium/Calmodulin-Dependent Protein Kinase II Autophosphorylation

Abstract: Experience-dependent plasticity can be induced in the barrel cortex by removing all but one whisker, leading to potentiation of the neuronal response to the spared whisker. To determine whether this form of potentiation depends on synaptic plasticity, we studied long-term potentiation (LTP) and sensory-evoked potentials in the barrel cortex of alpha-calcium/calmodulin-dependent protein kinase II (alphaCaMKII)T286A mutant mice. We studied three different forms of LTP induction: theta-burst stimulation, spike pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 36 publications
7
88
0
Order By: Relevance
“…However, there is evidence from whisker deprivation studies in barrel cortex that changes in spike timing drive in vivo plasticity rather than changes in input frequency (Celikel et al, 2004). Because spike timing-dependent plasticity (STDP) acts in a similar manner to other induction methods in barrel cortex (Hardingham et al, 2003) and it may be a more physiologically relevant induction protocol (Celikel et al, 2004), we used it in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there is evidence from whisker deprivation studies in barrel cortex that changes in spike timing drive in vivo plasticity rather than changes in input frequency (Celikel et al, 2004). Because spike timing-dependent plasticity (STDP) acts in a similar manner to other induction methods in barrel cortex (Hardingham et al, 2003) and it may be a more physiologically relevant induction protocol (Celikel et al, 2004), we used it in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we concentrated on LTP in adult (6 -13 weeks) rather than developing animals principally because it may relate to the adult plasticity induced in vivo in layer II/III cells by whisker deprivation (Hardingham et al, 2003). However, the majority of the literature on in vitro plasticity in neocortex relates to juvenile animals, and it may therefore be worthwhile to point out some of the differences between our observations and those made in juveniles.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Kinase activity has also been implicated in plasticity in the barrel cortex. Knock out or mutation (Glazewski et al, 2000;Hardingham et al, 2003) of calcium/calmodulin-dependent kinase II (CaMKII), an enzyme necessary for LTP (Malenka and Nicoll, 1999;Silva et al, 1992), blocks both receptive field plasticity and NMDA receptor-dependent LTP in barrel cortex. In addition, a recent study has identified a role for PKC in regulating synaptic strength at TC synapses in barrel cortex (Scott et al, 2006).…”
Section: Role Of Protein Kinases In Barrel Cortex Plasticitymentioning
confidence: 99%